Indonesian students’ learning attitude towards online learning during the coronavirus pandemic - Wijaya, Tommy Tanu; Zhou, Ying; Purnama, Aditya; Hermita, Neni (Research and Social Study Institute, 2020)
Now, the whole world is facing the coronavirus pandemic. In the meantime, students in China are required to do social distancing and not go to school. This coronavirus pandemic resulted in the use of online learning to teach students. In this research, we will get to know the students’ learning attitude towards online learning during the coronavirus pandemic. The sample population for this research are students in West Java, Indonesia. The data will be collected by using questionnaires and there was a total of 16 questionnaires that is collected for this research. The result of this research shows that online learning during this coronavirus pandemic is not very effective. Also, the students’ learning interest towards online learning is also very low. Based on the interview done on students and teachers, most of them stated that there are various factors that can affect online learning in China such as learning environment, internet and etc. The suggestion that is given in this research is that aside from online classes, teachers can also use video learning media that are used by developed countries so that it can solve the bad internet problem. The result of this research hopefully, can become a reference to improving a more effective learning media that can be used during the coronavirus pandemic in Indonesia.